Diversity of Marine 1,3-Xylan-Utilizing Bacteria and Characters of Their Extracellular 1,3-Xylanases - Sun, Hai-Ning; Yu, Chun-Mei; Fu, Hui-Hui; Wang, Peng; Fang, Zai-Guang; Zhang, Yu-Zhong; Chen, Xiu-Lan; Zhao, Fang (Frontiers in Microbiology, 2021)
1,3-xylan is present in the cell walls of some red and green algae and is an important organic carbon in the ocean. However, information on its bacterial degradation is quite limited. Here, after enrichment with 1,3-xylan, the diversity of bacteria recovered from marine algae collected in Hainan, China, was analyzed with both the 16S rRNA gene amplicon sequencing and the culture-dependent method. Bacteria recovered were affiliated with more than 19 families mainly in phyla Proteobacteria and Bacteroidetes, suggesting a high bacterial diversity. Moreover, 12 strains with high 1,3-xylanase-secreting ability from genera Vibrio, Neiella, Alteromonas and Gilvimarinus were isolated from the enrichment culture. The extracellular 1,3-xylanases secreted by Vibrio sp. EA2, Neiella sp. GA3, Alteromonas sp. CA13-2 and Gilvimarinus sp. HA3-2, which were taken as representatives due to their efficient utilization of 1,3-xylan for growth, were further characterized. The extracellular 1,3-xylanases secreted by these strains showed the highest activity at pH 6.0-7.0 and 30-40°C in 0-0.5 M NaCl. , exhibiting thermo-unstable and alkali-resistant characters. Their degradation products on 1,3-xylan were mainly 1,3-xylobiose and 1,3-xylotriose. This study reveals the diversity of marine bacteria involved in the degradation and utilization of 1,3-xylan, helpful in our understanding of the recycling of 1,3-xylan driven by bacteria in the ocean and the discovery of novel 1,3-xylanases.